Pengaruh Perintah Perjalanan Dinas Terhadap Peningkatan Motivasi Kerja Aparatur Sipil Negara Di Sekretariat DPRD Kabupaten Bengkalis - Tomisa, Muhammad Elsa; Nadrah, Nadrah (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2019)
The Secretariat of the Bengkalis Regency Regional Representative Council has used official travel orders as a step to increase work motivation of its employees or employees. In this research, the author wants to examine how official travel procedures are and whether there is an effect of providing official travel with work motivation by reason of wages in addition to their income, as well as an Islamic perspective on official travel. This study uses quantitative descriptive methods. From this study, it was found that the Secretariat of the Bengkalis Regency Regional Representative Office had used procedures in accordance with the Regulations of the Regent No. 82 of 2017. Then there was a significant influence of the Official Travel Order on Work Motivation of the Civil Civil Apparatuses in the Bengkalis Regency Regional Representative Council Secretariat. Meanwhile, according to the perspective of sharia, there is nothing wrong as long as it is run according to the rules.